Design optimization of Pixel Structure for α-Si based uncooled Infrared detector - Gupta, Sudha; Katiyar, Anupriya; Bhan, R. K.; Muralidharan, R. (Defence Science Journal, 2013)
In this paper authors present the design and simulation results achieved for pixel structure of amorphous Si (α-Si) based bolometer array. Most uncooled IR detectors in the world are based on VOx material. But this is not a standard material in IC technology and has many inherent disadvantages. The α-Si, an alternative material with high TCR is becoming as popular. However, large TCR values, in this material are achieved only in films of high resistivity. To achieve TCR value more than 2.5%/K, α-Si film resistivity is 80 ohms-cm. This gives rise to very large pixel resistance of the order of 100 Mega ohms depending upon the design of the leg structure. This high pixel resistance causes very large noise and hence lower sensitivity. If leg width or membrane thickness is increased in order to reduce the pixel resistance, then this results in higher thermal conductance which also decreases sensitivity. To overcome this problem, pixel structure is so designed that within a pixel, only part of the electrical conduction is through α-Si and rest is through metal. Simulation using Coventorware software has been done to optimize pixel resistance as well as thermal conductance through legs so that maximum sensitivity could be obtained. Optimization is also carried out in order to reduce sensitivity of pixel resistance to variation in material resistivity. Defence Science Journal, 2013, 63(6), pp.581-588, DOI:http://dx.doi.org/10.14429/dsj.63.5758